PENERAPAN PENDEKATAN STRUKTURAL METODE THINK PAIR SHARE (TPS) PADA MATERI LINGKARAN UNTUK MENINGKATKAN AKTIVITAS BELAJAR MATEMATIKA SISWA - Dewi Azizah (Delta: Jurnal Ilmiah Pendidikan Matematika, 2013)
The purposes of the research were to increase the students’ activities of learning mathematic and to improve students’ learning achievements by using TPS method. The research was a collaborative achievement research between the mathematic teacher, headmaster and the writer. The eighth grade students of SMP N 2 Wiradesa were the subject of the research. This research was a class action research. The results showed that TPS method could improve the students’ activities and achievements significantly. The students’ activities rose 34,15 % to 75,61% and students’ achievements rose from 36,59 % to 80,49%.